2020
DOI: 10.3390/molecules25204808
|View full text |Cite
|
Sign up to set email alerts
|

Chemical Defense Mechanisms and Ecological Implications of Indo-Pacific Holothurians

Abstract: Sea cucumbers are slow-moving organisms that use morphological, but also a diversecombination of chemical defenses to improve their overall fitness and chances of survival. Sincechemical defense compounds are also of great pharmaceutical interest, we pinpoint the importanceof biological screenings that are a relatively fast, informative and inexpensive way to identify themost bioactive organisms prior to further costly and elaborate pharmacological screenings. In thisstudy, we investigated the presence and abs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(20 citation statements)
references
References 94 publications
0
20
0
Order By: Relevance
“…In the last 5 years, several studies have been carried out with the aim of evaluating the bioactive properties of marine organisms. Several studies have tested the extracts and the isolated compounds from extracts of marine organisms for bioactivities [ 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 ], of which the cytotoxic activity [ 27 , 30 , 32 , 33 , 35 , 36 , 37 , 38 , 40 , 41 , 44 , 45 , 46 , 47 , 48 ] stands out. However, only in some studies was it possible to isolate the compounds and test them for cytotoxic activity [ 32 , 33 , 35 , 36 , 37 , 38 , 40 , 41 ].…”
Section: Secondary Metabolites From Marine Organisms With Cytotoxic Activitymentioning
confidence: 99%
“…In the last 5 years, several studies have been carried out with the aim of evaluating the bioactive properties of marine organisms. Several studies have tested the extracts and the isolated compounds from extracts of marine organisms for bioactivities [ 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 ], of which the cytotoxic activity [ 27 , 30 , 32 , 33 , 35 , 36 , 37 , 38 , 40 , 41 , 44 , 45 , 46 , 47 , 48 ] stands out. However, only in some studies was it possible to isolate the compounds and test them for cytotoxic activity [ 32 , 33 , 35 , 36 , 37 , 38 , 40 , 41 ].…”
Section: Secondary Metabolites From Marine Organisms With Cytotoxic Activitymentioning
confidence: 99%
“…As a continuation of our investigation of glycoside composition of the sea cucumber Thyonidium (=Duasmodactuyla) kurilensis (Levin), we report herein the isolation and structure elucidation of nine glycosides, kurilosides A 3 (1), D 1 (2), G (3), H (4), I (5), I 1 (6), J (7), K (8), and K 1 (9) as well as two desulfated derivatives, DS-kuriloside L (10) and DS-kuriloside As a continuation of our investigation of glycoside composition of the sea cucumber Thyonidium (=Duasmodactuyla) kurilensis (Levin), we report herein the isolation and structure elucidation of nine glycosides, kurilosides A3 (1), D1 (2), G (3), H (4), I (5), I1 (6), J (7), K (8), and K1 (9) as well as two desulfated derivatives, DS-kuriloside L (10) and DS-kuriloside M (11). The animals were collected near Onekotan Island in the Sea of Okhotsk.…”
Section: Introductionmentioning
confidence: 99%
“…The investigations of the triterpene glycosides from different species of sea cucumbers have a range of goals. Among them are the drug discoveries based on the promising candidates, demonstrating the target bioactivity [ 1 , 2 , 3 , 4 , 5 , 6 ], the solving of some taxonomic problems of the class Holothuroidea based on the specificity of the glycosides having characteristic structural peculiarities for the certain systematic groups [ 7 , 8 , 9 , 10 ], the ascertaining of biologic and ecologic functions of these metabolites [ 11 , 12 , 13 , 14 , 15 ], and the discovery of novel compounds, especially minor ones, that can be the “hot metabolites” clarifying the biosynthetic pathways of triterpene glycosides [ 16 , 17 , 18 ].…”
Section: Introductionmentioning
confidence: 99%
“…For example, effective antifoulants against barnacles and microfoulants (Oguri et al 2017) have been found in the red alga Laurencia sp. (Oguri et al 2017), tunicates (Levert et al 2020), the mollusk Phidiana militaris (Levert et al 2020), holothurians (Kamyab et al 2020), and sponges (Tintillier et al 2020). Antifoulants may improve the success of marine invasive tunicates (Utermann et al 2020;Nagai et al 2021).…”
Section: Chemical Defensementioning
confidence: 99%